THE EFFECT OF FIELD WORK PRACTICE AND PSYCHOLOGICAL CAPITAL ON WORK READINESS MEDIATED BY SOCIAL SUPPORT - Imarotuz Zakiyah; Novi Trisnawati; Lifa Panduwinata (Universitas Negeri Surabaya, 2025)
Phenomenon/Issue: The high open unemployment rate in Indonesian vocational schools and the direct absorption of SMKN 2 Buduran graduates majoring in Office Management and Business Services into workforce indicate the learners are still not showing their best performance even after completing vocational programs. Purpose: The purpose of this study is to investigate the influencees of Psychological Capital and Fiels Work Parctice on preparedness for the workforce, examining SMKN 2 Buduran grade XII students’ social support as a mediating factor Novelty: The novelty of this study lies in the integration of Field Work Practice, Psychological Capital, and social support into a single mediation model in the context of vocational school students, using multiple regression-based path analysis and bootstrapping through the PROCESS Macro. Research Methods: This study used an explanatory quantitative approach with subjects being grade XII Office Management and Business Services students who have completed Field Work Practice. Analyzed through classical assumption test, t-test, f-test, coefficient of determination, and path analysis. Results: The finding indicate that work readiness is not directly impacted by field work practice, while Psychological Capital and social support have a favorable and important impact. Simultaneously, Field Work Practice and Psychological Capital can explain around 73% of the differences in readiness for work. The impact of field work practice has been shown to be substantially mediated by social support, but the effect of psychological capital on Work Readiness is not mediated by social support. Research Contributions: Providing empirical evidence that strengthening Psychological Capital and structured social support around Field Job Practice implementation is important for designing school policies and strategic efforts to improve graduate work readiness